Characterizing Base in Warped Product Submanifolds of Complex Projective Spaces by Differential Equations - Ali H. Alkhaldi; Pişcoran Laurian-Ioan; Izhar Ahmad; Akram Ali (Mathematics, 2022)
In this study, a link between the squared norm of the second fundamental form and the Laplacian of the warping function for a warped product pointwise semi-slant submanifold <semantics>Mn</semantics> in a complex projective space is presented. Some characterizations of the base <semantics>NT</semantics> of <semantics>Mn</semantics> are offered as applications. We also look at whether the base <semantics>NT</semantics> is isometric to the Euclidean space <semantics>Rp</semantics> or the Euclidean sphere <semantics>Sp</semantics>, subject to some constraints on the second fundamental form and warping function.